Quantum model of PGM nanocluster and nanofilm formation in quartz: experimental verification of percolation conductivity - Yurov V.М.; Zhangozin, K.N. (Recent Contributions to Physics, 2026)
A quantum model is proposed for the formation of platinum-group metal (PGM) nanoclusters and nanofilms in quartz deposits. The model is based on the concept of a quantum surface nanolayer with characteristic thickness Rn ≈ 0.7–0.8 nm (Yurov). Within this nanolayer, discretization of electronic states, soliton-mediated transport, and surface premelting effects can stabilize continuous ultrathin films. The model is applied to the Taqyr-Qalzhyr deposit (Eastern Kazakhstan), where PGMs occur as nanometer-scale nanofilms and nanoclusters (on the order of single nanometers) with contents up to 66.5 ppm. Geochemical data indicate polygenetic origin: hydrothermal transport of Pd±Pt as chloride complexes and mechanical denudation of Ir–Os. The key prediction of the model—percolation conductivity through a nanocluster network—is consistent with electrohydraulic crushing results: ordinary quartz fractures along typical brittle trajectories, while Takyr-Kalzhyr samples disintegrate into ragged cellular structures, indicating contributions from tunneling/hopping transport.